An anode catalyst support for polymer electrolyte membrane fuel cells: application of organically modified titanium and silicon dioxide. Issue 42 (7th August 2019) - Malinowski, Marek; Iwan, Agnieszka; Hreniak, Agnieszka; Tazbir, Igor
Abstract : TiO2 and SiO2 act successfully as an anode support material despite their poor electrical properties providing the improvement of fuel cell electrochemical parameters. Abstract : This work describes an attempt to improve the physical and electrochemical parameters of PEM fuel cells that have electrodes modified by titanium and silicon dioxides. A customized design of membrane electrode assemblies was proposed which is characterized to have an around 6 times higher concentration of catalyst at the cathode side (2.0 mgPt cm −2 ) in order to investigate the influence of anode catalyst support treatment. Anode catalyst support materials were modified using pristine TiO2 and TiO2 –SiO2 –VTMS – the composite was crosslinked with the aid of vinyltrimethoxysilane. Surface area and porosity analysis was carried out with the aid of BET, BJH, t-plot and Horvath–Kawazoe (H–K) theories for particular components of the support materials and their catalyst mixtures. The experiment revealed a positive influence of TiO2 –SiO2 –VTMS (BET 321.9 m 2 g −1, BJH 3.7 nm) on the anode catalyst layer in terms of surface area (3-times increase, 75 m 2 g −1 ) and average pore size (decrease from 25.3 to 15.7 nm). Additionally, favourable microporosity (pores less than 2 nm) was introduced to the material according to the H–K analysis results (10.3 m 2 g −1, 0.65 nm). Electrochemical experiments, which include polarization curves, electrochemical impedance spectroscopy and cyclic voltammetry, have demonstrated the change of behaviour for the fabricated fuel cells with modified anodes against the reference sample. The mitigation of charge and mass transfer resistance (by 15–20%, 50 mV at 200 mA cm −2 ), the improvement of power density (up to 72%, 217 mW cm −2 ) and a better exposure of the catalyst to the reactants of an electrochemical reaction were observed for fuel cells modified by both pristine TiO2 and the hybrid TiO2 –SiO2 –VTMS-based compound.